Efektivitas Pemberian Aroma Terapi Lavender dan Teknik Counterpressure untuk Mengurangi Nyeri Persalinan Kala 1 di Klinik Fathma Medika - Nur Khasanah; Irfana Tri Wijayanti; Uswatun Khasanah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was to examine the effectiveness of lavender aromatherapy combined with counterpressure techniques in reducing labor pain during the first stage of labor. Labor pain during the active phase often increases anxiety, muscular tension, and maternal discomfort, and when unmanaged, may affect the progress of labor. Non-pharmacological approaches such as aromatherapy and counterpressure are increasingly recommended because they are safe, accessible, and support maternal relaxation. This study also aimed to compare pain intensity between mothers receiving the intervention and those who did not, providing practical evidence for midwifery practice. Materials and methods. This quasi-experimental study involved 36 primigravida mothers, divided equally into intervention and control groups. The intervention group received lavender aromatherapy through a diffuser along with counterpressure massage applied to the lower back during contractions, while the control group received routine care. Pain intensity was measured using a numerical pain scale before and after the intervention. Procedures followed standardized guidelines for lavender oil inhalation and counterpressure application, ensuring consistency throughout the active phase of labor . Results. The results showed a significant decrease in labor pain among the intervention group. Many mothers shifted from moderate or severe pain to mild or no pain. Statistical analysis using a T-test produced a T-value of 20.204 with p = 0.000 (α < 0.05), indicating a strong and significant effect of the intervention on pain reduction . Conclusions. Lavender aromatherapy combined with counterpressure is an effective non-pharmacological method for reducing pain during the first stage of labor. This technique can be recommended as supportive care to enhance maternal comfort and promote a more positive childbirth experience.